Kajian Ontologi,Epistamologi Dan Aksiologi Dalam Model Pembelajaran Role Playing Dalam Pembelajaran Bahasa Indonesia - Shafa Annawa Zahra Salsabila; Erna Ani Lestari; Siti Fatimatuzzahroh; Amrina Kholilina Rosada; Rani Setiawaty (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to understand the learning process of Indonesian language through Role Playing (RP) model by using ontology, epistemology, and axiology perspectives. The method applied in this study is Systematic Literature Review (SLR). Data were obtained from 24 articles accessed through Google Scholar and the Publish or Perish application as well as the mendeley application used to cite 24 journals with the keywords “Role Playing Learning Model in Indonesian Language Learning”. For data analysis, researchers reviewed relevant research results. The results showed that in terms of ontology, Role Playing functions as a social learning method that emphasizes students' active participation in living the character, which can improve imagination, empathy, and social skills. From an epistemological perspective, the Role Playing (RP) model is implemented through structured steps, including role assignment, group formation, role-playing, and reflection and evaluation of the learning experience. Axiology in this model is proven to have a positive impact on improving speaking skills, learning participation, and building students' confidence in the Indonesian language learning process.